Prenatal diagnosis and management of fetal hepatic haemangioma: a case report. (18th April 2012) - Mathew, V; Singh, T; Molykutty, T; Raveendran, M
Abstract : Background: Apart from some case reports describing the use of corticosteroids, there is very little information guiding antenatal management of fetal hepatic haemagiomas with arteriovenous malformations. We present management in a case of a liver haemangioma. Case: A 30-year-old woman, gravida 2 para 1, had an anomaly scan which showed cardiomegaly along with a 2x2cm cystic structure within the left lobe of the liver suggestive of a vascular liver haemangioma with evidence of arteriovenous malformation. A guarded prognosis was given for the pregnancy. After careful considerations, she opted to continue with the pregnancy and needed delivery at 32 weeks in view of an increase in size of the haemangioma (6x6cm), abnormal fetal arterial Dopplers and reduced fetal movements. The baby was noted to have deranged clotting and thrombocytopenia at birth and required fresh frozen plasma and platelet transfusions. A CT scan confirmed the presence of a liver haemangioma with arteriovenous malformation. As a result of the large size and vascularity of the haemangioma and the baby's poor condition, conservative management was continued and the parents were warned about the extremely guarded prognosis for the baby. Currently, the baby is 11 weeks old and is on digoxin for cardiac failure and propranolol to reduce angiogenesis and progression of the tumour. Although stable, the haemangioma is still too large for surgical intervention. Conclusion: Our case illustrates the various sequelae of the condition and the difficulties of antenatal management in the absence of good evidence.